The effects of farmland composition and heterogeneity on the density of three farmland bird species in Hungary - Erdős, Sarolta; Szép, Tibor; Báldi, András; Nagy, Károly (JOURNAL OF LANDSCAPE ECOLOGY, 2007)
The intensification of agriculture and change in the landscape may cause severe decline in farmland bird populations. Our primary goal was to examine the effects of farmland management and landscape composition and structure on the relative density of Skylark (Alauda arvensis), Tree Sparrow (Passer montanus) and Corn Bunting (Miliaria calandra). The common bird monitoring (MMM) was started in 1999 in Hungary, covering all major habitat types. We used this database for our analysis. The other database, that we used is the CORINE 1:50,000 Land Cover Map. We examined the effects of agricultural habitats (for example large arable fields, natural grasslands with trees and scrubs, small scale vineyards, homesteads, fruit and berry orchards), the number of patches and length of edges on the relative densities of the three species. Our results show that the habitat preference is species specific. Skylark strongly prefers large open habitats. The density of Corn Bunting correlated with the natural grasslands without trees and scrubs. The Tree Sparrow preferred small scale vineyards, and the large arable fields. We suggest that further information on the habitat preferences of these species are needed for their effective protection on farmland in Hungary.